Strategies of Nanocarrier-Based Therapeutic Drug Delivery - Salih, Walaa A.; Al-Taie, Alaa A. (Al-Nahrain Journal for Engineering Sciences, 2023)
In recent years, nanoparticles have gained significant attention in the field of cancer treatment due to their extensive potential and wide range of uses. The research mostly focuses on the inorganic chemicals, with a specific emphasis on metals, in order to enhance the comprehension of  functional nanoparticles synthesis. This undertaking is motivated by the distinctive characteristics exhibited by these materials, which provide significant advantages for both fundamental scientific inquiry and practical implementations, notably those focused on cancer. The objective of this review is to conduct a comprehensive analysis of the diverse applications of nanocomposites, with a specific focus on their utilization in medication delivery.